Removal of benzo [a]pyrene vapours from the air stream using the two-phase partitioning bioscrubber: an intervention study. Issue 18 (28th December 2022) - Mortazavi Mehrizi, Morteza; Yousefinejad, Saeed; Jahangiri, Mehdi; Karimi, Ali; Baghapour, Mohammad Ali; Jafari, Saeed; Jafarpor Baghdadabad, Fahime; Mahvi, Amir Hossein
ABSTRACT: In this study, the absorption of BaP in gas phase and biodegradation in liquid phase were examined in a bioscrubber. Important operational parameters including, input concentration (mg/m 3 ), output concentration (mg/m 3 ), pollutant load (g/m 3 .h), removal efficiency (%), removal capacity (g/m 3 .h) and biomass value (g/l) were examined. The results of the study showed that the BaP degrading strain performed better degradation by increasing the organic phase concentration and detention time. The results showed that the highest efficiency and removal capacity of bioscrubber occurred at 30% organic phase concentration. Furthermore, by increasing the organic phase concentration, the removal efficiency and capacity of the bioscrubber increased. The results of the study also showed that the removal efficiency of bioscrubber increased by increasing the organic phase concentration from 0%–10%, by increasing the concentration of 10%–20% is gradually increased, and by increasing the organic phase percentage to 30%, the efficiency increased sharply. The results indicated that TPPB can have an acceptable efficacy in removing BaP, which increases by increasing the organic phase concentration leading to more BaP removal.